Nuclear Medicine Technology Study Guide A Technologist$1 (Bs Review for Passing Board Exams /s - Moniuszko, Andrzej; Patel, Dharmesh; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Nuclear Medicine Technology Study Guide presents a comprehensive review of nuclear medicine principles and concepts necessary for technologists to pass board examinations. The practice questions and content follow the guidelines of the Nuclear Medicine Technology Certification Board (NMTCB) and American Registry of Radiological Technologists (ARRT), allowing test takers to maximize their success in passing the examinations. The book is organized by sections of increasing difficulty, with over 600 multiple-choice questions covering all areas of nuclear medicine, including radiation safety; radionuclides and radiopharmaceuticals; instrumentation and quality control; patient care; and diagnostic and therapeutic procedures. Detailed answers and explanations to the practice questions follow. Supplementary chapters include nuclear medicine formulas, numbers, and a glossary of terms for easy access by readers. Additionally, test-taking strategies are covered.
-- Tackling the Multiple-Choice Test -- Test I -- Test II -- Test III -- Formulas, Numbers, and Normal Range of Values -- Commonly-Used Abbreviations and Symbols in Nuclear Medicine -- Useful Websites.-.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Medicine & Public Health; Nuclear Medicine; Imaging / Radiology